Association between DDT or its byproducts and T2DM: a systematic review and meta-analysis - Tian, Weijian; Bai, Shaohui; Xie, Ting; Zha, Haolu; Yan, Zhouning; Zhang, Shengze; Wu, Nan; Yuan, Jianhui; Luo, Huanle; Xie, Qian; Jiang, Ying (Frontiers in Endocrinology, 2025)
BackgroundCurrently, type 2 diabetes mellitus (T2DM) is among the fastest-growing global health emergencies of the century. Emerging evidence from epidemiological studies suggests a potential positive association between exposure to dichlorodiphenyltrichloroethane (DDT) or its byproducts and an increasing risk of T2DM.ObjectiveWe conducted a systematic review and meta-analysis to quantify the association between DDT or its byproducts and T2DM. Additionally, we aimed to identify the sources of heterogeneity contributing to the inconsistency of the results.MethodsData analysis: assess the quality of the included studies using the Risk Of Bias In Non-randomized Studies of Exposure tool, determine the source of heterogeneity using subgroup analysis, sensitivity analysis and meta regression model based on a fixed-effects model, and analyze the publication bias using funnel plots, Egger’s test, and Begg’s test.ResultsDDT and its byproducts were associated with the risk of developing T2DM (total OR: 1.13, 95% CI: 1.08-1.15, I2 = 40%). Subgroup analysis stratified by biomarkers showed a stronger association between p,p′-DDE and T2DM (OR = 1.13, 95% CI: 1.09-1.17, I²= 58.5%). The results of the funnel plot, Egger’s test, and Begg’s test showed publication bias and small study effect in studies included in the analysis (p<0.05), but the influence on the results was smaller.ConclusionsThe systematic review and meta-analysis offer quantifiable proof of a positive correlation between exposure to DDT or its byproducts and a higher risk of developing T2DM.Systematic Review Registrationhttps://inplasy.com, identifier INPLASY20258004.